KONSEP TOLERANSI DALAM BUDAYA MELAYU - Hertina Hertina (Lembaga penelitian dan pengabdian kepada masyrakat, 2010)
Malays have different tolerance values are translated in a variety of vocabulary such as the value of openness, pluralism, persebatian, tolerant, cooperativeness, shared causes, shy, responsible, fair and true, brave and courageous, wise and prudent, meetings and consensus, taking advantage of the time, farseeing, industrious and diligent, trustworthy values, science, Takwa to God, and other. Tolerance in the life of wilt occupy an important position in the life of wilt, tolerant person who is considered a virtuous person, kind, know yourself and know the customs and religion holds, otherwise people who do not tolerate people who are not considered beperasaan, unsure of themselves and Nafsi called lust, selfish person. People like this will be abused in society and denigrated in the association. Another character of the Malays are tolerant. Malays would prefer to be silent rather than reactive. Reactive attitude in an environment can lead to an atmosphere of pros and cons. The atmosphere is always avoided by the Malays. In historical fact, are rarely found in incidents provoked by the Malays. There are factors adopted by the Malay people of faith that religion does not advocate violence and brutality.